2022
DOI: 10.1055/s-0042-1755368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Concentrations of Ropivacaine Used for Ultrasound-Guided Adductor Canal Block + IPACK Block in Total Knee Arthroplasty

Abstract: Introduction This study aimed to compare the analgesic efficacy of different concentrations of ropivacaine used for the combination of ultrasound-guided adductor canal block (ACB) and infiltration between the popliteal artery and capsule of the posterior knee (IPACK) block in total knee arthroplasty (TKA). Materials and Methods Before general anesthesia, 90 patients undergoing TKA were randomized to receive ACB + IPACK block with ropivacaine 0.2, 0.25, or 0.3% (defined as group A, B, and C, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Disease Markers response. Taken together, it has implied that preoperative ACB coupled with general anaesthesia could reduce the stress response generated by surgery and maintain the intraorganic environment [14,15]. In this study, no comparison of the use of other intraoperative anaesthetics was conducted to confirm alternative approaches to the suppression of surgical stress with anaesthesia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Disease Markers response. Taken together, it has implied that preoperative ACB coupled with general anaesthesia could reduce the stress response generated by surgery and maintain the intraorganic environment [14,15]. In this study, no comparison of the use of other intraoperative anaesthetics was conducted to confirm alternative approaches to the suppression of surgical stress with anaesthesia.…”
Section: Discussionmentioning
confidence: 90%
“…The findings of this study disclosed that the plasma adrenaline and norepinephrine concentrations in group B were elevated compared to the preoperative period, differentially with group A, which indicated that group A exhibited a milder stress response. Taken together, it has implied that preoperative ACB coupled with general anaesthesia could effectively reduce the stress response generated by surgery and maintain the intraorganic environment [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%